Channel estimation for long term evolution downlink receiver system performance - N, Prabakaran; S, Sivakannan; Fernandes J, Bennilo; G, Thirugnanam (International Journal of Engineering and Technology, 2017)
3GPP LTE is the advancement of the UMTS because of everâ€increasing requests for brilliant interactive media administrations as indicated by client's desires. Since downlink is dependably an essential factor in scope and limit viewpoints, extraordinary consideration has been given in choosing innovations for LTE downlink collector. In this paper, LTE-downlink receiver framework exhibitions of Channel Response estimations are tried and assessed utilizing FDD transmission plans. An insertion calculation is utilized to acquire all Channel Response estimations. In this model direct addition calculations utilized as a part of recurrence and image area. The high information rates and the high limit can be accomplished by utilizing the upsides of the two advances. These advances have been chosen for LTE downlink receiver. Pilotâ€assisted channel estimation is a strategy in which known signs, called pilots, are transmitted alongside information to get channel learning for legitimate deciphering of got signals. This paper goes for channel estimation for LTE downlink receiver framework. The execution of the framework recreated in various remote channel models that comprises of AWGN, RAW AWGN and Veh A channels. The execution of the framework is assessed utilizing distinctive regulations, for example, QPSK, 16 QAM and 64 QAM. Execution of these calculations has been measured as far as Bit Error Rate (BER) Vs Eb/No.